2020
DOI: 10.1371/journal.pone.0225301
|View full text |Cite
|
Sign up to set email alerts
|

Real-world cost-effectiveness of rivaroxaban compared with vitamin K antagonists in the context of stroke prevention in atrial fibrillation in France

Abstract: ObjectiveThe objective was to assess the real-world cost-effectiveness of rivaroxaban, versus vitamin K antagonists (VKAs), for stroke prevention in patients with atrial fibrillation (AF) from a French national health insurance perspective.Funding: LF, CC and PL received honorarium from Bayer AG for critical input into study design and results analysis. Bayer Plc. provided support in the form of salaries for author KB; Bayer AG provided support in the form of salaries for author JBB. Bayer AG sponsored the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…This confirms previous results submitted to NICE [12,13], but also results published later, in the UK in particular [46], but also in France [15]. This latter paper used a similar approach for rivaroxaban, considering only RWE inputs (characteristics, clinical event rates, treatment effect, discontinuation, switch rates, utility, resource use and unit costs for all events), and led to a similar conclusion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This confirms previous results submitted to NICE [12,13], but also results published later, in the UK in particular [46], but also in France [15]. This latter paper used a similar approach for rivaroxaban, considering only RWE inputs (characteristics, clinical event rates, treatment effect, discontinuation, switch rates, utility, resource use and unit costs for all events), and led to a similar conclusion.…”
Section: Discussionsupporting
confidence: 88%
“…As described elsewhere [ 15 ], the model comprises a series of health states based on potential complications of NVAF (stable AF, acute and post-major ischaemic stroke [IS], acute and post-minor IS, acute and post-myocardial infarction [MI], acute and post-intracranial haemorrhage [ICH] and gastrointestinal [GI] bleed), and the absorbing state of death ( Figure 1 ). Patients transition through the model in cycles of 3 months, accumulating quality-adjusted life years (QALYs) associated with each health state, together with the costs of treatment, events and subsequent monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Using real-world data (RWD), the impact of anticoagulant therapy has been analyzed using different sources (9)(10)(11)(12)(13)(14)(15). Electronic health records (EHRs) collect a large amount of information, including data about prevalence, disease control, risk factors, treatments, modifying conditions, and information for surveillance programs (16,17). All of these can aid in evaluating treatment performance outside of the controlled environment of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that DOACs tend to be more cost-effective than VKAs for the treatment of AF. [ 19 23 ] One of these studies suggest that rivaroxaban is cost-effective compared to VKA, although the type of AVK and the dose thereof are not specified. [ 23 ] A comparative study of the cost-utility of the first 3 DOACs to be marketed in Spain (apixaban, dabigatran and rivaroxaban), [ 24 ] found dabigatran to be the most cost-useful.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 23 ] One of these studies suggest that rivaroxaban is cost-effective compared to VKA, although the type of AVK and the dose thereof are not specified. [ 23 ] A comparative study of the cost-utility of the first 3 DOACs to be marketed in Spain (apixaban, dabigatran and rivaroxaban), [ 24 ] found dabigatran to be the most cost-useful. [ 25 ] However, the most recent study carried out in Spain does not show significant differences between dabigatran and AVKs.…”
Section: Introductionmentioning
confidence: 99%